Moderasi Al-Qur’an Dalam Perspektif Historis Mikro: Implikasi Asbāb Al-Nuzūl Bagi Pendidikan Islam - Mashfiyatus Shidqiyyah; Diana Puspita Kusuma Wardani; Muhammad Farih (PT. Pusmedia Group Indonesia, 2026)
This study aims to analyze the principle of moderation (wasathiyah) in the Qur'an through a micro-historical approach to asbab al-nuzul (the reasons for the revelation). By focusing on specific events that led to the revelation of certain verses, this study argues that moderation is not merely an abstract theological concept, but an operational principle that was directly implemented in shaping the early Muslim community. Through case studies in the fields of worship, social affairs, and law, this article shows how the Qur'an's response to the socio-historical reality of Jahiliyyah Arab society always prioritized balance, justice, and rejection of extremism (ghuluw). In conclusion, understanding asbab al-nuzul in micro terms is a key methodology for capturing the Qur'an's universal message of moderation that is relevant in the current context.